Fermentative quality of silage as affected by protein level in the ensiled material: A meta-analysis. Issue 1 (March 2020) - Jayanegara, A; Wardiman, B; Kondo, M; Ridla, M; Nahrowi,; Laconi, E B
Abstract: Ensiling of high-protein forages like alfalfa, indigofera, cassava and moringa, however, are characterized by considerable extent of proteolysis. This study aimed to perform a meta-analysis from various published experiments regarding the effect of protein level on fermentative quality of silage. Papers reported data on protein contents of silages and their fermentative characteristics were collected and integrated in a database. A total of 15 papers and comprised of 155 data points were included. The ensiled materials were peas, wheat, barley, maize, sorghum, alfalfa and mucuna. The ensiling period varied from 20 to 303 days. Data were statistically analyzed by using the mixed model methodology. Studies from different papers were treated as random effects whereas protein level in silage was treated as fixed effect. The model statistics used was p-value. Results revealed that higher protein level led to an increase of DM loss in silage (p<0.01). Protein was negatively correlated with NDF (p<0.001) and ADF (p<0.05). Increasing protein level elevated pH value of the silage (p<0.05) and tended to increase acetate concentration (p<0.1). Ethanol concentration was elevated by increasing silage protein level (p<0.05). Higher silage protein level increased organic matter digestibility (OMD), lactic acid bacteria (LAB) population, nitrate and ammonia concentrations of the silage (p<0.05). It can be concluded that higher protein level induces proteolysis in the silage and reduces its fermentative quality.